What type of online sales promotion do airline users prefer? Analysis of the moderating role of users’ online experience level - Esmeralda Crespo-Almendros; Salvador Del Barrio-García; Juan Miguel Alcántara-Pilar (Tourism & Management Studies)
The aim of the present research is to assess which type of online promotional incentive (monetary or non-monetary) is the most effective at achieving purchase intention for airline tickets, depending on the user’s level of Internet experience (characterized as novice, moderate, or expert user). A Univariate General Linear Model is conducted, using data obtained from an experimental design with two levels: monetary online sales promotion and nonmonetary online sales promotion. The findings indicate that in the case of acquiring an airline ticket online, monetary incentives are more appealing to novice Web users, while non-monetary incentives are preferred by expert users. The present study breaks new ground in that it examines, in the travel sector, the effectiveness of online sales promotions at prompting the individual to purchase online, in a comparative analysis based on online sales incentive type (monetary vs. non-monetary). The work contributes to the literature on the online travel sector by analyzing how the user’s level of Web experience affects the effectiveness of each type of online sales promotion.